Analisis Tindak Tutur Lokusi dalam Video Kelas Psikologi Positif pada Kanal YouTube Garvin Goel - Chelsea Olivia Ramadhani; Harlin Nur Afizah; Khonitah Nuril Hidayati; Rizka Ari Yani; Inara Faridotu Rohmah; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Universitas Palan, 2026)
The analysis of locutionary speech acts is a pragmatic study that can reveal the role of digital communication in the learning process, particularly in educational videos such as the Positive Psychology Class on the YouTube channel Garvin Goei. Within this video, there are various forms of utterances, such as declarative, interrogative, and imperative, which serve to convey information clearly and build understanding among viewers. The accurate formulation of locutionary utterances will also influence the effectiveness of online learning, necessitating an in-depth analysis to assess their quality. The objective of this research is to identify the forms and functions of locutionary speech acts present in the video, which can subsequently be used as a reference in designing educational content. Good quality locutionary speech acts will impact learners' comprehension and interaction abilities in a distance learning context. The methodology employed is a descriptive qualitative approach, beginning with data collection through observation and note-taking techniques on the Garvin Goei YouTube video. The observation technique involves reading and observing the entire video content, while the note-taking technique includes recording locutionary utterances and re-verifying the obtained findings. After conducting the analysis, 606 data points of locutionary speech acts were obtained, with a dominance of declarative sentences (213), interrogative (145), and imperative (88), indicating variations in sentence structure and the use of conjunctions. The quality of these utterances is evaluated based on clarity of meaning, pragmatic function, and level of complexity. The results of this research are expected to serve as a reference for teaching materials and provide deeper insights into the influence of locutionary speech acts on the quality of digital educational communication.